A Human-Centered Design Approach to Creating Tools to Help Journalists Monitor Digital Political Ads: Insights and Challenges. Issue 3 (16th March 2023) - McKernan, Brian; Stromer-Galley, Jennifer; Korsunska, Ania; Bolden, Sarah E.; Rossini, Patrícia; Hemsley, Jeff
Abstract: Political actors have increasingly incorporated digital advertising into their persuasive efforts. Greater transparency of how political actors are using digital ads is necessary given concerns that they may be using digital ads to suppress voter turnout and spread disinformation and xenophobia. We apply a human-centered design framework to identify the design requirements necessary to create tools that satisfy journalists' needs for covering digital political ads. Based on interviews with journalists, our findings indicate that they are interested in covering how political actors are using digital advertising as well as reporting on the platforms, such as their policies. Our findings also reveal serious obstacles that impede journalists' ability to effectively cover digital political advertising. From the currently available tools, journalists we interviewed found it difficult to quickly identify key takeaways that could result in or contribute to stories. Journalists also need information that the most popular technology platforms do not offer. Supporting journalists' efforts to provide greater transparency of digital political ads will require a collective effort on the part of designers and technology platforms to provide information that journalists need via tools that surface and synthesize this information in a way that satisfies journalists' professional demands.